2012
DOI: 10.1039/c2cp23190e
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in different domains of truxenone supramolecular assembly on Au(111)

Abstract: The two-dimensional assemblies of truxenone, diindeno[1,2-a;1',2'-c]fluorene-5,10,15-trione, on the Au(111) surface have been studied by scanning tunnelling microscopy in ultrahigh vacuum. It is found that the truxenone monolayer on Au(111) exhibits different two-dimensional supramolecular structures. The investigation using scanning tunnelling microscopy combined with the density functional theory calculations can be a helpful approach to understand the complicated supramolecular structures of truxenone self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…It has been previously reported that when immobilised on a surface the truxenone molecule forms two enantiomers and that it may be these which are responsible for the different packing. 20 Discrimination between the two enantiomers is not possible from our STM images and although theoretical calculations have been previously employed the authors concluded that the energetic difference between enantiomorphous and enantiopure molecule pairs and assemblies are negligible when compared to the molecule-substrate interaction. Our data demonstrate that the supramolecular structures present on Cu (111) can accommodate both enantiomers.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It has been previously reported that when immobilised on a surface the truxenone molecule forms two enantiomers and that it may be these which are responsible for the different packing. 20 Discrimination between the two enantiomers is not possible from our STM images and although theoretical calculations have been previously employed the authors concluded that the energetic difference between enantiomorphous and enantiopure molecule pairs and assemblies are negligible when compared to the molecule-substrate interaction. Our data demonstrate that the supramolecular structures present on Cu (111) can accommodate both enantiomers.…”
mentioning
confidence: 86%
“…STM images show that the molecules appear triangular and are oriented in a honeycomb structure dened by a rhombic twomolecule unit cell (r 1 ¼ r 2 ¼ 2.04 nm from LEED, r 1 ¼ 2.07 nm AE 0.1 nm from STM) similar to that observed in the work on Au (111)/Mica of Chen and co-workers. 20 The LEED pattern collected from this surface shows a primitive (8 Â 8) pattern indicative of commensurate epitaxial order between the truxenone molecules and the Cu (111). No annealing procedure was required to produce a sharp LEED pattern, however where annealing was undertaken (190 C for 10 minutes) with 4 minute growth time the LEED pattern remained unchanged.…”
mentioning
confidence: 94%
“…Each F 3truxenone molecule appeared as a three-lobed triangular feature with a less bright central region rather than the single bright triangular shape as previously observed for truxenone. 24,25 This additional contouring in the local density of states (LDOS) of the molecule may be due to the uorine atoms creating an uneven distribution of electron density in the outermost phenyl rings with respect to the core. 26,27 Whether this effect is an electronic or local structural effect is problematic to discern with STM measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Truxenone formed six-fold close-packing domains on Au(111) in an exact or slight displacing edge-edge arrangement. 23 Mixing 2,3,7,8,12,13hexahexyloxy-truxenone (TrO23) with copper phthalocyanine (CuPc) or 1,3,5-tris(R-carboxydecyloxy)benzene (TRCDB, R = different alkyl chain), TrO23 assembled into molecular lines or networks depending on types and concentrations of other components. 24,25 Further study indicated that the chirality in the basic structure motif formed with numbers of T10CDB (TRCDB, R = 10), TrO23 and CuPc molecules was kept and amplified in following hierarchical structures.…”
Section: Introductionmentioning
confidence: 99%